Investigation on the Sulfuric Acid Corrosion Mechanism for Concrete in Soaking Environment. (7th May 2018) - Min, Hongguang; Song, Zhigang
Abstract : This paper chooses the apparent diffusion coefficient for OH − (hydroxyl ion) for concrete as an index to evaluate the corrosion degree of concrete subjected to sulfuric acid. Based on the reaction boundary layer theory, a sulfuric acid corrosion model for concrete was established and verified through experiments. The experiment design and data processing of sulfuric acid corrosion tests for concrete were carried out using uniform test design and nonparametric regression. Effects of water-cement ratio and pH value are presented on the sulfuric acid corrosion mechanism for concrete. Test results show that when the pH value was 2.50, the sulfuric acid corrosion degree of concrete was the most serious. The boundary layer effect always existed in the sulfuric acid corrosion for concrete, and the corrosion process included rapid and stable corrosion stages. The apparent diffusion coefficient for OH − for concrete increased with the decrease of pH value and the increase of water-cement ratio and cement proportion.